Memahami Kritik dan Kemarahan Interpersonal di Balik Pesan-Pesan Humoris via New Media: Kasus hashtag di Twitter #ThePowerofSetnov dan #TiangListrik - Khairul Arief Rahman (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2022)
This paper will explore issues related to how anger can be an interpersonal power through humorous messages on social media. The existence of new media that makes it easier for anyone to access and process information, of course has real implications related to cooperation or in the Indonesian context it can be said as mutual cooperation. In the context of Indonesia, where people like humor, interpersonal communication in new media makes criticism and anger unique. This humor automatically has its own strength as part of the interpersonal communication culture in Indonesia. The creation of various topics on Twitter such as #ThePowerOfSetnov and #TiangListrik is one of the cases where personal anger is manifested in the form of humor. So that the main concentration in this discussion is how the message of interpersonal humor is interpreted as part of anger in the context of interpersonal communication and how the function of humor in the context of interpersonal communication is carried out on social media. The conclusion is that the humorous interpersonal messages in the topics of #ThePowerOfSetnov and #SaveTiangListrik are a mixture of various things between criticism, personal dissatisfaction, and the oddities found in the case that ensnared Setya Novanto. However, because of the oddity or strangeness, directly between individuals try to find a suitable logic by equating the case with something that did not happen or an imaginative analogy. Keywords: Collectivity, Interpersonal Communication, Hyperpersonal, Humor, and Social Media